NILAI-NILAI PENDIDIKAN KARAKTER DALAM BUKU TEKS BAHASA INDONESIA KURIKULUM MERDEKA KELAS VII SMP - Ismiana; Djumingin, Sulastriningsih; Saleh, Muhammad (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research aims to examine the values of character education and describe the implementation of character education values contained in the Indonesian language textbook Merdeka Curriculum for Class VII SMP. This research uses a qualitative type of research using a descriptive design. The data collection technique used is documentation, reading and note taking. The results of the research show that the character education values contained in the Independent Curriculum Indonesian Language Textbook for Class VII SMP are: religiosity, nationalism, integrity, independence and mutual cooperation. Meanwhile, the implementation of the character education values contained in the Indonesian Language Textbook, Independent Curriculum for Class VII SMP, is carried out and implemented in the school, family and community environment.